2013
DOI: 10.1039/c3dt52208c
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic pyridyltriazole–Cu(ii) dimers as supramolecular hosts

Abstract: Tetradentate bis(pyridyltriazole) ligands containing aromatic spacers of different sizes react with Cu(2+) to produce metallo-supramolecular hosts that bind 1,4-diazabicyclo[2.2.2]octane molecules internally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The measurements were carried out in DMF (0.1 M Bu 4 NPF 6 ), with glassy carbon working electrode, Ag/AgCl reference electrode, and Pt wire counter electrode. The ligand, m-xpt, was synthesized by using a literature procedure 21 . Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements were carried out in DMF (0.1 M Bu 4 NPF 6 ), with glassy carbon working electrode, Ag/AgCl reference electrode, and Pt wire counter electrode. The ligand, m-xpt, was synthesized by using a literature procedure 21 . Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of using two molecules of binuclear Cu(I) complex for reductive coupling of CO 2 molecules as depicted in Bouwman's work, we wished to prepare a single macrocyclic complex that can serve as a host for CO 2 reduction. We chose the m-xylylene group as a spacer to connect our two pyridyltriazole chelating units 21 . Other researchers have used multifunctional ligands to control the spatial position of two metal centres.…”
mentioning
confidence: 99%
“…Maverick and co-workers have synthesised similar [Cu 2 L 2 ] 4+ macrocycles from Cu(II) ions and bis-(2-pyridyl-1,2,3-triazole) ligands, incorporating either a m-xylene (1,3-) or 2,7-dimethylnaphthalene spacer unit. 28 The larger cavity of the naphthalene-based metallo-macrocycle enabled binding of DABCO and other guests, with the guest bridging the two internal axial sites of the Cu(II) metal ions, while the xylyl-based system was too small. However, this smaller system (Fig.…”
Section: Metallocyclesmentioning
confidence: 99%
“…We [39][40][41][42][43][44] and others [45][46][47][48][49][50][51][52][53][54][55] have explored the use of 1,4-disubstituted 1,2,3-triazole containing ''click'' ligands in the development of functionalized metallosupramolecular architectures and have shown that metallomacrocycles, cages and helicates can be readily generated. As part of that work we developed a small family of bis-2-(1-R-1H-1,2,3-triazol-4-yl)pyridine ligands 1 [56] (Scheme 1) and showed that they would assemble into [Fe 2 L 3 ] 4+ metallosupramolecular helicates [57] when treated with Fe(II) ions.…”
Section: Introductionmentioning
confidence: 99%